UPAYA GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 5 DI MI RAUDLATUSSHIBYAN - Insani, Haeriyah Nurul; Herianingtyas, Nur Luthfi Rizqa (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
This research aims to find out how teachers/educators improve the reading skills of grade 5 students. This research was conducted using descriptive qualitative methods as the main method. The technique used in collecting data in this research was the interview technique, with grade 5 teachers, interviews were conducted to obtain information from the teacher about the efforts they made. The results of this research show that it is important to carry out literacy activities in the reading corner/school library at several times a week, so that children get used to reading and they are free to choose what books they want to read, accompanied/supervised by the teacher. Apart from that, in determining the appropriate reading level for grade 5 students, it is important to choose reading books that are appropriate to the conditions or needs and characteristics of each student